A Middle and Late Devensian sequence from the northern part of Kents Cavern (Devon, UK) - Rob Dinnis; John Boulton; Barry Chandler; Jesse Davies; Jennifer C. French; Thomas Higham; Louisa Jáuregui; Mark Lewis; Matthias Meyer; Danielle Schreve; Chris Stringer; Chris Proctor (Journal of Quaternary Science, 2025)
1920s/30s excavation of a Middle Devensian sequence in the northern part of Kents Cavern recovered important Late Middle and Early Upper Palaeolithic archaeological material, including Britain's oldest known Homo sapiens remains. Questions remain about this material, including how it came to be in the cave. Judged by the recorded distribution of finds it may have entered via the Northeast Gallery. A previously unrecorded entrance into the cave from the Northeast Gallery was identified in 2014, and a column through the entrance's sedimentary fill was excavated during 2015–2016. The results of that work are reported here. The entrance retains an intact and well‐stratified Pleistocene sequence comparable to the ‘Cave Earth’ unit described previously inside the cave. The uppermost part of the newly recognised Northeast Gallery entrance sequence has been removed by historical excavation, with most of the remaining sediments spanning the Middle Devensian and earlier part of the Late Devensian. The sequence contains bone and pollen, and ancient mammalian DNA is preserved within the sediments. The base of the Northeast Gallery entrance sequence is formed of a clayey diamict comparable to the cave's ‘Breccia’ unit, a deposit currently understood as Middle Pleistocene, and previously identified only in Kents Cavern's southern chambers. Comparison of the excavated sequence with the historical record of the Vestibule excavation shows that the basal cave earth deposits in the Northeast Gallery entrance are significantly higher than those inside the cave. Although requiring further work to confirm, this suggests that the Northeast Gallery could have played a major role in the accumulation of material in the Vestibule during the Middle Devensian.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Physical, Chemical and Compaction Characteristics of Slightly Weathered Tephras of New Zealand - Shaurya Sood; Gabriele Chiaro; Thomas Wilson; Mark Stringer (Geotechnical and Geological Engineering, 2024)
The North Island of New Zealand is a region of high volcanic activity, with significant eruptions over the past. Analogous to past events, future volcanic eruptions would produce a considerable volume of ash and granular soils, covering widespread areas and raising concerns for their disposal and storage. Such deposits, primarily airfall tephra, could be potentially used in geotechnical engineering applications such as foundations, roadway embankments and land reclamations. However, before their use as structural fills can be recommended, detailed laboratory investigations of their physical, chemical, compaction, and geotechnical engineering properties (strength, compressibility, collapsibility, liquefaction potential, etc.) must be conducted. Different tephra deposits can be products of different eruptions, so chemical composition analyses can be combined with the physical, compaction, and engineering properties to characterize such deposits. Accordingly, this paper provides useful insights from physical (grain size, specific gravity, and morphology), chemical (elemental and mineralogy using X-ray fluorescence and X-ray diffraction), and compaction tests (maximum dry density, optimum water content, and particle breakage) for eleven selected volcanic tephra samples sourced from the North Island of New Zealand in the Rotorua, Taupo, and Auckland regions.

Controls on Water Levels and Salinity in a Barrier Island Mangrove, Indian River Lagoon, Florida - Christina E. Stringer; Mark C. Rains; Sarah Kruse; Dennis Whigham (Wetlands, 2010)

Impact of depth of pedigree and inclusion of historical data on the estimation of additive variance and breeding values in a sugarcane breeding program - Felicity Claire Atkin; Mark J. Dieters; Joanne K. Stringer (Theoretical and Applied Genetics, 2009)

Historical land use and soil analysis guiding corridor landscape design - J. Renee Keydoszius; S. Knight Cox; Mary B. Haque; Elena Mikhailova; Christopher J. Post; William C. Stringer; Mark A. Schlautman (Urban Ecosystems, 2007)

Feasibility of Tissue Plasminogen Activator Formulated for Pulmonary Delivery - John S. Dunn; Rajiv Nayar; Jackie Campos; Brooks M. Hybertson; Yue Zhou; Mark Cornell Manning; John E. Repine; Kathleen A. Stringer (Pharmaceutical Research, 2005)